1988
DOI: 10.1111/j.1525-1314.1988.tb00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic evolution of the Attic Cycladic Metamorphic Belt on Naxos (Cyclades, Greece) utilizing 40Ar/39Ar age spectrum measurements

Abstract: U'Ar/"Ar age spectrum analysis of phengite separates from Naxos, part of the Attic Cycladic Metamorphic Belt in Greece, indicates that cooling following high-pressure, low-to medium-temperature metamorphism, M I , occurred about 50 Ma ago. Phengite has *"AT* gradients that suggest that part of the scatter observed in conventional K-Ar ages was caused by diffusion of radiogenic argon from the minerals during a younger metamorphism, M2. In central Naxos, this metamorphism ( M 2 ) has overprinted the original min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 50 publications
4
153
0
2
Order By: Relevance
“…Wijbrans & McDougall (1988) and later Lister & Baldwin (1993) (Wijbrans & McDougall 1988) and Ios (Baldwin & Lister 1998) of the Greek Cyclades and the D'Entrecasteaux Islands of New Guinea (Lister & Baldwin 1993). In addition, sensitive highresolution ion microprobe U/Pb work carried out on migmatites from Naxos by Keay et al (2001) has demonstrated a number of distinct zircon overgrowth events associated with numerous brief metamorphic heating episodes (on Barrovian geotherms) spanning a period of about 4 Ma.…”
Section: Bimodal Heating In Barrovian-type Settingsmentioning
confidence: 99%
“…Wijbrans & McDougall (1988) and later Lister & Baldwin (1993) (Wijbrans & McDougall 1988) and Ios (Baldwin & Lister 1998) of the Greek Cyclades and the D'Entrecasteaux Islands of New Guinea (Lister & Baldwin 1993). In addition, sensitive highresolution ion microprobe U/Pb work carried out on migmatites from Naxos by Keay et al (2001) has demonstrated a number of distinct zircon overgrowth events associated with numerous brief metamorphic heating episodes (on Barrovian geotherms) spanning a period of about 4 Ma.…”
Section: Bimodal Heating In Barrovian-type Settingsmentioning
confidence: 99%
“…1990; Wijbrans and McDougall, 1988). Large-scale isoclinal folds and other deformation structures formed during D1 were overprinted by top-to-north shearing of D2, starting at the onset of crustal thinning and post-orogenic extension in the early Miocene (Mercier et al, 1976;Ring et al, 2010;Urai et al, 1990).…”
Section: Geological Settingmentioning
confidence: 99%
“…The latter was partly accreted to the Pelagonian nappe contributing to the building of the Hellenides, while its buried part underwent early Eocene HP-LT metamorphism recorded in the Cycladic Blueschists unit and the Cycladic basement [Bonneau and Kienast, 1982;Bonneau, 1984;Wijbrans and McDougall, 1988;Tomaschek et al, 2003;Lagos et al, 2007]. These units were then progressively exhumed up to the end of the Eocene in the Cyclades and in the Olympos, Ossa and Pelion tectonic windows as a synorogenic extrusion wedge bounded by the Vari detachment on top (in Syros) and the SCSZ at the base (in Ios) (figure 9) Ring et al, , 2010Brun and Faccenna, 2008;Huet et al, 2009;Jolivet and Brun, 2010].…”
Section: A Continuous Subduction Migrating Southwardmentioning
confidence: 99%
“…~15-20 kbar, ~500 °C) whose metamorphic peak is dated at ~50 Ma, forming the Cycladic Blueschists unit and the Cycladic basement [Bonneau and Kienast, 1982;Bonneau, 1984;Wijbrans and McDougall, 1988;Tomaschek et al, 2003;Lagos et al, 2007]. Exhumation of these metamorphic units first occurred between 45 and 35-30 Ma in a syn-orogenic context, following a cold retrograde path (figure 5) [Altherr et al, 1979;Bonneau and Kienast, 1982;Avigad and Garfunkel, 1989;Trotet et al, 2001].…”
Section: Accepted Manuscriptmentioning
confidence: 99%